2016
DOI: 10.1038/ncomms12805
|View full text |Cite
|
Sign up to set email alerts
|

Real-time encoding and compression of neuronal spikes by metal-oxide memristors

Abstract: Advanced brain-chip interfaces with numerous recording sites bear great potential for investigation of neuroprosthetic applications. The bottleneck towards achieving an efficient bio-electronic link is the real-time processing of neuronal signals, which imposes excessive requirements on bandwidth, energy and computation capacity. Here we present a unique concept where the intrinsic properties of memristive devices are exploited to compress information on neural spikes in real-time. We demonstrate that the inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 45 publications
(55 reference statements)
1
130
0
Order By: Relevance
“…Indeed, it has even been suggested that memristance effects can explain spiketiming-dependent plasticity behaviour 34 . To date, many researchers have investigated memristor-based SNNs through full-system simulations using experimental device parameters 29,35,36 , although large-scale implementations are still limited.…”
Section: Nature Electronicsmentioning
confidence: 99%
“…Indeed, it has even been suggested that memristance effects can explain spiketiming-dependent plasticity behaviour 34 . To date, many researchers have investigated memristor-based SNNs through full-system simulations using experimental device parameters 29,35,36 , although large-scale implementations are still limited.…”
Section: Nature Electronicsmentioning
confidence: 99%
“…It is important to predict and tailor the reaction of memristive devices to the action of real electrical signals, when trying to couple the memristive devices with biological cultures and tissues to organize an adaptive interface not only for the processing [49], but also for the classification and stimulation of the electrical activity of brain cells. There are a new physics and new applications behind such neurointerfaces on the basis of memristive devices.…”
Section: Noise-induced Phenomenamentioning
confidence: 99%
“…This waveform was employed to validate the concept of memristive integrated sensors. Reproduced with permission . Copyright 2016, Springer Nature.…”
Section: Current State Of Memristive Systems For Neuromorphic Computingmentioning
confidence: 99%